Campur Kode Sebagai Media Promosi Dalam Akun Nanti Kita Sambat Tentang Hari Ini - Zahro, Fanisa Qorina; Solihati, Nani (Universitas Negeri Padang, 2024)
This research was aims to look at code mixing as a promotional medium in the Nanti Kita Sambat Tentang Hari Ini account and what impact is felt through the use of code-mixing. The method used in this research is descriptive qualitative with data collection techniques, namely observing and noting techniques. The listening technique is used to listen to uploads that use code mixing and the note-taking technique is used to describe the results of the code-mixing analysis as promotional media for the Nanti Kita Sambat Tentang Hari Ini account. The results of the study show that in the later, we will meet about today account, there is a form of code mixing between Javanese and Indonesian. The use of code mixing is used as a promotional medium. As a result, the number of followers of social media accounts increased, cooperation with large companies was established, and the products offered at the Sumber Sambat Lokapasar were sold out.